2013
DOI: 10.1039/c3cc42689k
|View full text |Cite
|
Sign up to set email alerts
|

A series of new star-shaped or branched platinum–acetylide derivatives: synthesis, characterization, and their aggregation behavior

Abstract: A series of branched or star-shaped platinum-acetylide derivatives were successfully prepared and their aggregation behaviour both in solution and on the surface was explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The absorption spectra of Pt-1 show the weak absorption peaks at the higher energy region, ca. 280–320 nm, which are likely due to 1 π–π* and n−π* transitions localized on alkoxyphenyl components . The strongest absorption bands at about 430 nm predominantly arise from the 1 MLCT (dπ­(Pt) → π*­(triazine) and dπ­(Pt) → π*­(fluorene acetylide)) and 1 LLCT (phenyl acetylide ligand to fluorene acetylide) transitions and 1 ILCT (fluorene acetylide charge transfer to fluorene acetylide) transitions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The absorption spectra of Pt-1 show the weak absorption peaks at the higher energy region, ca. 280–320 nm, which are likely due to 1 π–π* and n−π* transitions localized on alkoxyphenyl components . The strongest absorption bands at about 430 nm predominantly arise from the 1 MLCT (dπ­(Pt) → π*­(triazine) and dπ­(Pt) → π*­(fluorene acetylide)) and 1 LLCT (phenyl acetylide ligand to fluorene acetylide) transitions and 1 ILCT (fluorene acetylide charge transfer to fluorene acetylide) transitions.…”
Section: Resultsmentioning
confidence: 99%
“…280−320 nm, which are likely due to 1 π−π* and n−π* transitions localized on alkoxyphenyl components. 19 The strongest absorption bands at about 430 nm predominantly arise from the 1 MLCT (dπ(Pt) → π*(triazine) and dπ(Pt) → π*(fluorene acetylide)) and 1 LLCT (phenyl acetylide ligand to fluorene acetylide) transitions and 1 ILCT (fluorene acetylide charge transfer to fluorene acetylide) transitions. Noticeably, it was found that in the absorption spectrum of Pt-1 appeared a very weak tail beyond 550 nm.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a continuing study, a series of branched or star-shaped platinum-acetylide derivatives, 47 and 48 (Chart 15), were successfully prepared and their aggregation behavior both in solution and on the surface was investigated. 68 Interestingly, concentration-dependent emission properties were observed for these complexes in some solutions, indicating the existence of certain aggregates in the selected solvents. For instance, the emission spectrum of 47a displayed a red shift of 34 nm with a decreased intensity upon increasing the concentration, which might be attributed to their tendency to self-associate through p-p interactions between neighbouring molecules in the concentrated solution.…”
Section: Supramolecular Self-assembly Of Platinum-acetylide Building ...mentioning
confidence: 96%